2022
DOI: 10.1371/journal.pntd.0010630
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of nodding syndrome in the Greater Mundri area, South Sudan: Prevalence, spatial pattern and environmental risk factors

Abstract: Background Nodding syndrome (NS) is a progressive neurological disease that has been described in several sub-Saharan African counties, but South Sudan is considered the most affected. However, knowledge about the exact burden and the epidemiological risk factors of NS in South Sudan is lacking. Objective To determine the prevalence, distribution and epidemiological risk factors of NS in the Greater Mundri area, the epicenter of NS in South Sudan. Methods A NS prevalence house-to-house survey was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…However, several previous studies have reported a significantly strong association between NS and onchocerciasis [ 1 ]. The possible link of NS with the river has been confirmed by our most recent study in the Mundri area [ 6 ]. Also, a study in Maridi, in the Western Equatoria region of South Sudan, has reported that this link is with the blackfly breeding site at the Maridi dam [ 26 ].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…However, several previous studies have reported a significantly strong association between NS and onchocerciasis [ 1 ]. The possible link of NS with the river has been confirmed by our most recent study in the Mundri area [ 6 ]. Also, a study in Maridi, in the Western Equatoria region of South Sudan, has reported that this link is with the blackfly breeding site at the Maridi dam [ 26 ].…”
Section: Discussionsupporting
confidence: 59%
“…Previously, we investigated epidemiological risks for NS at the household level, looking into socioeconomic status; source of water for drinking, cooking, and bathing; nutritional status; internal displacement; river distance; and CDTI. Ownership of poultry, behaviors around the rivers; and living near the rivers increased the risk of having NS in a household [ 6 ]. Here, we investigate the clinical characteristics of nodding syndrome (NS), individual-level risk factors, access to treatment, and perceptions about NS.…”
Section: Introductionmentioning
confidence: 99%
“… 31 , 32 Moreover, from the larger epidemiological study in which the current study was embedded, less than half of households used ivermectin in the last five years, and its use was equal between cases and matched household and community controls. 4 Given the conflicting evidence from our and previous case-control studies, we urge that any interventions to prevent or reduce the NS burden are part of prospective randomized trials which are required to definitively proof or disprove causality.…”
Section: Discussionmentioning
confidence: 93%
“… 1–3 In high prevalence areas, one in five households can be affected. 4 Clinical features of NS may include atonic seizures with head nodding, other seizures types, cognitive deficits and stunted growth, and parkinsonism in advanced stages. 2 Patients are often stigmatized, isolated and sexually abused.…”
Section: Introductionmentioning
confidence: 99%
“…Although not discussed by Edridge et al , 1 two of the authors reported previously an association between nodding syndrome in Mundri County and use of river water for drinking, cooking, hand washing and bathing. 11 Since South Sudan is permeated by rivers, but nodding syndrome is largely confined to parts of Western Equatoria, there must be other factors that drive the selective geographic risk for this childhood brain disease. One important consideration is that, prior to 1990, nodding syndrome was unknown in Mundri County, 2 a region impacted by episodic civil conflict resulting in population displacement reflected in widely different prevalence rates of nodding syndrome (2.3–13.7%).…”
mentioning
confidence: 99%